Importance of Schottky barriers for wide-bandgap thermoelectric devices - Wais, M. (2019)
The development of thermoelectric devices faces not only the challenge of optimizing the Seebeck coefficient, the electrical and thermal conductivity of the active material, but also further bottlenecks when going from the thermoelectric material to an actual device, e.g., the dopant diffusion at the hot contact. We show that for large bandgap thermoelectrics another aspect can dramatically reduce the efficiency of the device: the formation of Schottky barriers. Understanding the effect, it can then be fixed rather cheaply by a two-metal contact solution.